Acquisition of conditioned taste aversion in rats is prevented by tetrodotoxin blockade of a small midbrain region centered around the parabrachial nuclei - Ivanova, S F; Bures, J (Physiology & behavior, 1990)
A remarkable feature of conditioned taste aversion (CTA) is the resistance of the association between the gustatory trace and symptoms of poisoning against disruptive procedures. In an attempt to identify the neural substrate of this phase of CTA acquisition, thirsty rats were offered 0.1% saccharin for 15 min, were immediately afterwards anesthetized with pentobarbital, received stereotaxic injections of tetrodotoxin (TTX, 10 ng/microliters) into various brainstem regions and were poisoned with IP injection of LiCl (0.15 M, 2% body weight). In Experiment 1, TTX prevented CTA acquisition when injected into the parabrachial nuclei but was ineffective in the lower medulla. TTX alone did not elicit CTA even at brain sites in which it caused death in 30% of the animals. In Experiment 2, the brainstem was systematically explored by a grid of bilateral TTX injections. A spatial gradient of the CTA disruption pointed to the parabrachial nuclei as the brain region responsible for the amnesic effect observed. Experiment 3 showed that a single TTX injection into the parabrachial nucleus on one side did not prevent CTA acquisition and that similarly ineffective were TTX injections in the sagittal plane both at the mesencephalic and bulbar levels. It is concluded that the pivotal role of the parabrachial nuclei in the formation of the permanent CTA engram can only be revealed by functional blockade which is more radical than that achieved during general anesthesia.
Keywords: Injections; Water Deprivation; Tetrodotoxin; mozek; Lithium; lithium; Chlorides; Sodium Channels; chloridy; sodíkové kanály; chuť; Lithium Chloride; krysa rodu Rattus; mezencefalon; chlorid lithný; injekce; zvířata; Avoidance Learning; tetrodotoxin; učení vyhýbat se; Male; Taste; Brain; Rats; Animals; deprivace z nedostatku vody; mužské pohlaví; Mesencephalon